DETERMINING FACTORS OF CONSTRUCTION MARKET DEVELOPMENT - Voronkov, O.; Dolyna, B. (Municipal economy of cities. Series: «Economy science», 2022)
The article reviews the scientific literature on the study of factors in the development of construction markets. The analysis of trends in the development of the construction market in Ukraine was carried out, according to the results of which it was established that this market is rapidly developing today. The structure of the completed construction work has been investigated, as a result of which it has been established that in recent years there has been an increase in the share of construction of engineering structures. In the structure of work on the construction of buildings, the share of construction of non-residential objects is growing, and the share of residential construction is decreasing. A hypothesis about the structure of factors influencing the development of the construction market is considered. Selected factors are systematized into categories such as financial, economic and social. The results of the correlation analysis of factors influencing the development of the construction market are presented. It was found that such factors as average wages, incomes and expenses of the population, gross domestic product, index of construction products and population size have a high level of correlation between the resulting indicator of the development of the construction market. Correlation analysis of selected factors showed a close correlation between them and the resulting indicator of the construction market. Conclusions are drawn and prospects for the development of the research are determined. According to the results of the study the goals and objectives of further study of the factors of development of construction markets are determined. This is a key decision in developing a strategy for development over a long period of time.